0425 Actigraphy Assessment in Fibromyalgia: A Standardized Protocol to Reduce Discrepancies between Subjective and Objective Sleep. (12th April 2019) - McGovney, Kevin D; Curtis, Ashley F; McCann, Dillon; McCrae, Christina S
Abstract: Introduction: Discrepancies between self-reported and actigraphy assessed sleep are common in patients with fibromyalgia (FM). This may partially be due to methods of actigraphy analysis, which often use non-standardized accelerometry algorithms that do not accurately estimate rest intervals (i.e., bedtime/waketime interval), and lead to inaccurate computation of sleep variables. Here, we describe the MizZzou Sleep Lab Actigraphy Protocol (MSLAP) as an alternative to automated rest interval detection (AUTO). Application of MSLAP relative to AUTO was carried out in a sample of patients with FM. For each method, magnitude of discrepancies between actigraphy/self-reported sleep were compared. Methods: Fourty-seven adults with FM completed three days of actigraphy and sleep diaries measuring bedtime, waketime, SOL, sleep efficiency (SE), wake after sleep onset (WASO), and total sleep time (TST). For actigraphy analysis, rest intervals were determined using MSLAP and AUTO (in Philips Actiware V.6.0.8). MSLAP determines probable bedtimes/waketimes using a hierarchical procedure: 1) visually inspect activity/light signal, 2) identify trigger value where activity/light reaches zero (bedtime), or activity/light exceeds 100 or 1uW/cm 2 (waketime), 3) detect ten consecutive subsequent epochs meeting sub/supra-threshold criteria for activity/light. For MSLAP and AUTO, bedtime and waketime were recorded, and SOL, SE, WASO, and TST were computed using validated Actiware sleep scoring algorithms. Paired t-tests determined whether magnitude of subjective/objective sleep outcome discrepancies differed between MSLAP and AUTO. Results: Bedtime objective/subjective discrepancies were lower (p<.001) for MSLAP (M=32.7mins, SD=36.0) relative to AUTO (M=55.4mins, SD=79.3). Waketime discrepancies were also lower (p<.001) for MSLAP (M=23.3mins, SD=40.5) relative to AUTO (M=40.5mins, SD=71.5). SOL discrepancies were lower (p=.04) for MSLAP (M=43.0mins, SD=35.1) relative to AUTO (M=47.4mins, SD=36.7). Subjective/objective discrepancies between MSLAP and AUTO did not differ for SE, WASO, or TST. Conclusion: Compared to automated accelerometry rest interval detection algorithms, MSLAP may reduce discrepancies between self-reported and actigraphically assessed sleep in FM. Results promote the use of MSLAP in actigraphy analysis, which may help clinicians assess and treat sleep disorders in patients with chronic pain. Support (If Any): NIAMS (R01AR055160/R01AR005160-S1;PI, McCrae). Data collected at the University of Florida (Clinical Trial-NCT02001077;PI, McCrae).